Development Strategies and Natural Resources: a Critical Review of the Literature - Lorenzo Mancini (Papeles de Europa, 2014)
From the dawn of the economic science, natural resources have been at the centre of the analysis by scholars. During last years, the boom of the extractive sector has given a renewed momentum to the debate about economic implications of those recourses, while a series of initiatives linked with that sector has been spreading. This paper critically studies the main contributions of the cientific literature on the relation between natural resources and development strategies. The objective is to identify and systematize those conditions that could promote an economic development process, defined as a structural change, based on the exploitation of thos resources.